2021
DOI: 10.1212/wnl.0000000000012765
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cognitive Reserve on the Association of Vascular Brain Injury With Cognition

Abstract: Objective:To determine whether cognitive reserve attenuates the association of vascular brain injury with cognition.Methods:Cross-sectional data were analyzed from two harmonized studies: the Canadian Alliance for Healthy Hearts and Healthy Minds (CAHHM) and the Prospective Urban and Rural Epidemiology (PURE) study. Markers of cognitive reserve were education, involvement in social activities, marital status, height, and leisure physical activity, which were combined into a composite score. Vascular brain inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 38 publications
2
17
1
Order By: Relevance
“…Cognitive reserve is a theoretical concept that explains the individual differences in maintaining cognitive function in the face of brain pathology. First, greater CR appears to be associated with better cognitive performance in WMH subjects 6,8,9 . Second, CR may act as a moderator between the burden of WMH and cognitive performance.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Cognitive reserve is a theoretical concept that explains the individual differences in maintaining cognitive function in the face of brain pathology. First, greater CR appears to be associated with better cognitive performance in WMH subjects 6,8,9 . Second, CR may act as a moderator between the burden of WMH and cognitive performance.…”
Section: Introductionmentioning
confidence: 97%
“…First, greater CR appears to be associated with better cognitive performance in WMH subjects. 6,8,9 Second, CR may act as a moderator between the burden of WMH and cognitive performance. A more significant burden of WMH links to poorer cognitive performance in subjects with low CR.…”
Section: Introductionmentioning
confidence: 99%
“…Third, the elderly individuals included in the present study all had a relatively high level of education. Previous evidences indicated that high education was one of strongest marker of cognitive reserve which may shape cognitive aging trajectories (Durrani et al, 2021;Farfel et al, 2013;Singh-Manoux et al, 2011). Therefore, future studies would be pro t from a larger adult sample with wide levels of education.…”
Section: Limitation and Future Directionmentioning
confidence: 99%
“…Thus, low educational attainment is another potential confounder in the association between CKD and cognitive disorders with some evidence of synergy as subtle GFR decline is associated with more rapid cognitive decline in those with lower educational levels (54). However, more recent data in the general population suggests that higher cognitive reserve may not diminish the adverse effects of covert vascular brain injury (55).…”
Section: Education Levelmentioning
confidence: 99%